Alterations of the Gut Microbiota in Multiple System Atrophy Patients - Wan, Linlin; Zhou, Xin; Wang, Chunrong; Chen, Zhao; Peng, Huirong; Hou, Xuan; Peng, Yun; Wang, Puzhi; Li, Tianjiao; Yuan, Hongyu; Shi, Yuting; Hou, Xiaocan; et al. (Frontiers in Neuroscience, 2019)
Multiple system atrophy (MSA) is a fatal neurodegenerative disease, and the pathogenesis is still quite challenging. Emerging evidence has shown that brain–gut–microbiota axis served a pivotal role in neurological diseases, however, researches utilizing metagenomic sequencing to analyze the alteration in gut microbiota of MSA patients were quite rare. Here, we carried out metagenomic sequencing in feces of 15 MSA patients and 15 healthy controls, to characterize the alterations in gut microbial composition and function of MSA patients in mainland China. The results showed that gut microbial community of MSA patients was significantly different from healthy controls, characterized by increased genus Akkermansia and species Roseburia hominis, Akkermansia muciniphila, Alistipes onderdonkii, Streptoococcus parasanguinis, Staphylococcus xylosus, while decreased genera Megamonas, Bifidobacterium, Blautia, Aggregatibacter and species Bacteroides coprocola, Megamonas funiformis, Bifidobacterium pseudocatenulatum, Clostridium nexile, Bacteroides plebeius, Granulicatella adiacens. Further, functional analysis based on KEGG database revealed aberrant functional pathways in fecal microbiome of MSA patients. In conclusion, our findings provided evidence for dysbiosis in gut microbiota of Chinese MSA cohorts, and helped develop new testable hypotheses on pathophysiology of MSA.